Thomas T. Craven papers - Craven, Thomas T. (Thomas Tingey), 1873-1950.
Correspondence, memoranda, writings, orders, reports, biographical and genealogical materials, newspaper clippings, and other materials relating primarily to Craven's World War I convoy duty in Atlantic and Mediterranean waters (1917-1918), his command of the United States Naval Aviation Forces in Europe (1918), his command of a gunboat flotilla on the Yangtze River, China (1929-1931), and his service as chief coordinator of the U.S. Federal Coordinating Service, Bureau of the Budget. Topics also include the court-martial of Edward H. Watson, commander of Destroyer Squadron 11 which shipwrecked at Point Honda, Calif. (1923), investigation of Husband Edward Kimmel following the 1942 Japanese attack on his Pacific Fleet command, curriculum reform at the United States Naval Academy, New York State Maritime Academy, merchant marine, Alaska fisheries, aircraft carriers, radio communications policy, and corrupt practices in naval shipyards. Correspondents include Richard E. Byrd, Hutchinson I. Cone, Morris L. Cooke, Josephus Daniels, Ralph Earle, Stanford C. Hooper, Herbert Hoover, Dudley W. Knox, Frank Knox, David Sarnoff, and William S. Sims.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Byrd, Richard Evelyn, -- 1888-1957 -- Correspondence; Cone, Hutchinson Ingham, -- 1871-1941 -- Correspondence; Cooke, Morris Llewellyn, -- 1872-1960 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Earle, Ralph, -- 1874-1939 -- Correspondence; Hooper, Stanford Caldwell, -- 1884-1955 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Kimmel, Husband Edward, -- 1882-1968.; Knox, Dudley Wright, -- 1877-1960 -- Correspondence; Knox, Frank, -- 1874-1944 -- Correspondence; Sarnoff, David, -- 1891-1971 -- Correspondence; Sims, William Sowden, -- 1858-1936 -- Correspondence; Watson, Edward H. -- 1873-1942.; United States. -- Bureau of the Budget. -- Federal Coordinating Service; United States. -- Navy -- Foreign service -- China -- Yangtze River; United States. -- Navy. -- Destroyer Squadron 11.; United States. -- Navy. -- Naval Aviation Forces; United States. -- Navy. -- Pacific Fleet; New York State Maritime Academy; United States Naval Academy -- Curricula; Aircraft carriers; Budget -- United States; Courts-martial and courts of inquiry; Fisheries -- Alaska; Gunboats; Merchant marine -- United States; Naval convoys -- Atlantic Ocean; Naval convoys -- Mediterranean Sea; Navy-yards and naval stations, American -- Corrupt practices; Pearl Harbor (Hawaii), Attack on, 1941.; Radio -- Law and legislation -- United States; Shipwrecks -- California -- Honda, Point; World War, 1914-1918 -- Naval operations, American; World War, 1939-1945 -- Naval operations, American; Naval officers